A Rare Case of Lateral Sinus Thrombosis with Carotid Space Abscess. (24th October 2012) - Singh, Gautam Bir; Rai, Anil K.; Singh, Sarvejeet; Sinha, Mukul
Abstract : This case report describes a case of carotid space abscess secondary to lateral sinus thrombosis associated with internal jugular vein thrombosis. With this case, we illustrate a rare entity that presented in an extremely rare manner. To the authors knowledge such a case has not been previously reported.